PKM SOCIALIZATION OF EARTHQUAKE AND TSUNAMI DISASTER EVACUATION IN THE MENTAWAI ISLANDS - Elviyanti , Elviyanti; Armizoprades, Armizoprades; Elimarni, Elimarni; Hafiz Maulana; Al Azha; Zootan Ahmad; M Fauzi7; Ryan Dio Pratama; Delvi Novita (Ikatan Dosen Menulis, 2024)
This community service program aims to improve disaster preparedness and response in Bukit Pamewa Village, North Sipora District, Mentawai Islands Regency, which is an area prone to earthquakes and tsunamis. This activity includes outreach, training and disaster response simulations which aim to equip the community with knowledge and skills in dealing with potential natural disasters. Through socialization, the community gains an understanding of disaster risks and the preventive actions that must be taken. Emergency response training involves all levels of society, including the formation of a Village Disaster Response Team whose task is to lead evacuations and provide first aid in emergency situations. Disaster simulations were carried out to practice evacuation steps in real-time, which succeeded in showing increased community preparedness. The results of this activity show that the people of Bukit Pamewa Village now have better knowledge and skills in responding to disasters, including the ability to evacuate and use safety equipment. Apart from that, the formation of the Village Disaster Response Team is an important asset in increasing community preparedness. It is hoped that this program can become the basis for further development to make Bukit Pamewa Village a resilient community and ready to face future disasters.